Avaliação de impacto dos projetos produtivos do Programa de Combate à Pobreza Rural no Estado da Bahia : avanços e limitações - Bicalho, Ellenise Elsa Emídio (Universidade Federal de São Carlos, 2016)
This thesis aimed to evaluate the socioeconomic impacts of the productive projects of the Rural Poverty Combat Program in Bahia (Produzir-III). Poverty in Brazil is concentrated in the North and Northeast regions, and the state of Bahia has the largest number of individuals in this situation. The Produzir-III is a project focused on rural poverty combat in the Northeast and aimed to finance social projects, production, and infrastructure, at no cost and with decentralized governance. The main benefit is a project grant that is given to a community association. A community association is responsible for the implementation, maintenance, and management of its project. Therefore, calls up that the community organization enables the generation of social capital and thus empowerment of beneficiaries. To achieve the proposed objectives were carried out of cases and survey studies. The case studies were chosen intentionally and performed in 2013, with seven studied projects. Additionally, in 2014, 27 projects, of which 19 mechanization projects, 5 of flour mills and three honey processing units, provided data for economic and financial analysis. The selection of the project was performed to comprise each type of productive Produzir-III project. Data were analyzed from the net cash flow, discounted by the methods of Internal Rate of Return. The survey was conducted in October and November 2013. The survey sample included two groups: beneficiary households and the control group (non-beneficiary households). Beneficiaries were selected from productive projects. A control group is a comparison group, which has similar characteristics to those of beneficiaries. Members of this group were selected after the selection of beneficiaries. Data analysis was performed using descriptive statistics of selected indicators for the two groups, and the measurement of impacts. Before measuring the impact, the two samples (beneficiaries and control) were paired, and then the difference in difference method was performed. The results showed that the associations face difficulties regarding collective and financial management of the project, mainly associated with low level of education and under-utilization of projects. The results of the statistical analysis show that the majority of household heads are male, with an average age around 50 years; low level of education; whose main occupation is farming, working on their own. These characteristics are consistent with the poor people in rural areas. Finally, the difference in differences analysis showed that the productive projects had positive impacts on most of the selected indicators. However, the impact was significant at 5% for housing and housing conditions; car ownership, refrigerator, satellite dish and cattle, pigs, goats, sheep; and associative experience. In general, the impacts of Produzir-III were small and in few respects.
Keywords: Pobreza rural; Política pública; Avaliação de impacto; Rural poverty; Public policy; Impact assessment; ENGENHARIAS::ENGENHARIA DE PRODUCAO